Development of Analytical Model for Modular Tank Vehicle Carrying Liquid Cargo - Toumi, Messaoud; Bouazara, Mohamed; Richard, Marc J. (My University, 2013)
The study of dynamics of tank vehicles carrying liquid fuel cargo is complex. The forces and moments due to liquid sloshing create serious problems related to the instability of tank vehicles. In this paper, a complete analytical model of a modular tank vehicle has been developed. The model included all the vehicle systems and subsystems. Simulation results obtained using this model was compared with those obtained using the popular TruckSim software. The comparison proved the validity of the assumptions used in the analytical model and showed a good correlation under single or double lane change and turning manoeuvers
Keywords: Analytical Model; Tank Vehicle; Stability; Dynamic Behavior; Suspension